A Comprehensive Systematic Review of The Relationship between Substance Addiction and The Risk of Major Depressive Disorder - Humaira Madina Liza Lubis; Ni Putu Intan Sri Maharani (The International Journal of Medical Science and Health Research, 2026)
Introduction: Substance addiction represents a significant public health burden globally, with a well-documented comorbidity with Major Depressive Disorder (MDD). Understanding the nature and strength of this relationship within specific populations, such as in Indonesia, is crucial for developing targeted interventions. Methods: This systematic review followed a structured protocol to examine the relationship between substance addiction and the risk of MDD in Indonesian populations. We screened studies based on predefined criteria focusing on adult populations, diagnosed substance use disorders, validated depression measurements, and quantitative association measures. A total of 21 studies (20 cross-sectional, 1 case-control) were included. Data on substance details, depression assessment, association findings, population characteristics, study design, and moderating factors were extracted and synthesized. Results: The review revealed a high prevalence of depression among individuals with substance use disorders, particularly in clinical settings (e.g., 84.6% in drug abusers in rehabilitation) (Dinda Iryawati Bedy Saskito et al., 2009). Most studies reported a significant positive association. For instance, substance use was associated with a 6.5-fold increased risk of mental health disorders (A. Triana et al., 2019), and tobacco smoking with a prevalence ratio of 1.28 for depressive symptoms (Trisna Simanjuntak et al., 2023). Dose-response relationships were observed, linking longer duration and heavier use with more severe depression (Made Adi Wiratama et al., 2015; Adelia azis Azis Nasution et al., 2020). Family social support was identified as a significant protective factor (Shuci Rachmawati et al., 2016). Discussion: The findings consistently point towards a strong link between substance addiction and increased risk of MDD in Indonesia, with variations explained by population context, substance type, and methodology. The evidence supports both self-medication and substance-induced pathways. The protective role of social support highlights the importance of psychosocial interventions. Conclusion: Substance addiction is significantly associated with an elevated risk of Major Depressive Disorder in Indonesian adults, with the strength of association influenced by substance type, use patterns, and psychosocial context. Integrated treatment addressing both substance use and depression, alongside strengthening family support systems, is strongly recommended.